Published works - Nelson, Alexander (The University of Edinburgh, 1948)
PRINCIPLES OF AGRICULTURAL BOTANY (1946) • FERTILITY IN THE GENUS BRASSICA. FROM JOURNAL OF GENETICS, Vol.. xviii No. 2, JUNE, 1927. • FERTILITY IN THE GENUS BRASSICA (With One Plate and Seven Text-figures). BY ALEXANDER NELSON. (1927)